2017
DOI: 10.1128/jvi.00770-17
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus Establishes Persistent Infection in Tumor Cells In Vitro : Contribution of the Cleavage Site of Fusion Protein and Second Sialic Acid Binding Site of Hemagglutinin-Neuraminidase

Abstract: Newcastle disease virus (NDV) is an oncolytic virus being developed for the treatment of cancer. Following infection of a human ovarian cancer cell line (OVCAR3) with a recombinant low-pathogenic NDV, persistent infection was established in a subset of tumor cells. Persistently infected (PI) cells exhibited resistance to superinfection with NDV and established an antiviral state, as demonstrated by upregulation of interferon and interferon-induced genes such as myxoma resistance gene 1 (Mx1) and retinoic acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…The differential pathogenicities of these isolates suggested that NDV evolves in its natural host (duck) to increase its survival rate. Similar results describing NDV persistent infection due to a modification in the genome have been shown in an ovarian cell line (Rangaswamy et al., ), but persistent infection in ducks, geese or chickens has yet to be studied. Our chicken‐origin NDV isolate did not evolve in ducks, and thus, it caused high mortality.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The differential pathogenicities of these isolates suggested that NDV evolves in its natural host (duck) to increase its survival rate. Similar results describing NDV persistent infection due to a modification in the genome have been shown in an ovarian cell line (Rangaswamy et al., ), but persistent infection in ducks, geese or chickens has yet to be studied. Our chicken‐origin NDV isolate did not evolve in ducks, and thus, it caused high mortality.…”
Section: Discussionsupporting
confidence: 64%
“…A mutation in the stalk region of the HN protein modulates the fusion process and expression of the HN‐F complex on the cellular surface (Iorio, Melanson, & Mahon, ; Mirza & Iorio, ). Previous studies have revealed that the amino acid residues at 169, 174, 175, 192, 198, 236, 258, 299, 317, 401, 416, 498, 516, 517, 519, 526, 552, 553 and 557 are important for HN protein function (presented in red in Figure b) (Connaris et al., ; Estevez, King, Luo, & Yu, ; McGinnes & Morrison, ; Rangaswamy et al., ; Takimoto, Taylor, Connaris, Crennell, & Portner, ; Zaitsev et al., ). In the present study, we identified amino acid substitutions at positions 9, 323, 331 and 514 when we compared the Ch/CH/SD/2008/128 and Du/CH/SD/2009/134 isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, a persistent NDV infection was successfully established in one ovarian cancer cell line, OVCAR3, while other cell lines, such as OAW28, CAL27, FaDu, and PE/CA PJ15, were unable to establish a persistent infection (47). PI cells can have an altered antiviral state induced by low levels of IFN production and the presence of IFN-stimulated genes, as seen in the case of NDV infection (47,48). The P/V-CPI Ϫ virus is a potent inducer of IFN (18), and work is in progress to understand the role that this cytokine plays in the differential ability to establish P/V-CPI Ϫ PI cells in different cancer cell lines.…”
Section: Discussionsupporting
confidence: 64%
“…Host cell type can also be key in developing a persistent paramyxovirus infection (46). Consistent with this, a persistent NDV infection was successfully established in one ovarian cancer cell line, OVCAR3, while other cell lines, such as OAW28, CAL27, FaDu, and PE/CA PJ15, were unable to establish a persistent infection (47). PI cells can have an altered antiviral state induced by low levels of IFN production and the presence of IFN-stimulated genes, as seen in the case of NDV infection (47,48).…”
Section: Discussionmentioning
confidence: 56%
“…The NDV genome contains six genes encoding the nucleoprotein (NP), phosphoprotein (P), matrix protein (M), fusion protein (F), hemagglutinin-neuraminidase protein (HN) and large RNA polymerase (L) (Dimitrov et al, 2019). Infection of host cells by NDV is accomplished by the interaction of two surface glycoproteins, F and HN (Gravel and Morrison, 2003;Rangaswamy et al, 2017). The F protein directs the viral fusion activity and is supposed to play a major role in determining NDV virulence (Samal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%